2009
DOI: 10.1074/jbc.m109.003384
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Activity of the Prototypic Cyclotide Kalata B1 Is Modulated by the Formation of Multimeric Pores

Abstract: The cyclotides are a large family of circular mini-proteins containing a cystine knot motif. They are expressed in plants as defense-related proteins, with insecticidal activity. Here we investigate their role in membrane interaction and disruption. Kalata B1, a prototypic cyclotide, was found to induce leakage of the self-quenching fluorophore, carboxyfluorescein, from phospholipid vesicles. Alanine-scanning mutagenesis of kalata B1 showed that residues essential for lytic activity are clustered, forming a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
200
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(214 citation statements)
references
References 45 publications
11
200
2
Order By: Relevance
“…Such a mechanism of action is consistent with their hemolytic properties (6) and ability to disrupt gut epithelial cells in lepidopteron larvae (3) and is further supported by a range of biophysical studies (12)(13)(14)(15). The prototypic cyclotide kalata B1 (kB1) 7 is the most well studied cyclotide, and it has been shown to bind to (12) and disrupt phospholipid bilayers by a pore-forming mechanism (15).…”
mentioning
confidence: 63%
“…Such a mechanism of action is consistent with their hemolytic properties (6) and ability to disrupt gut epithelial cells in lepidopteron larvae (3) and is further supported by a range of biophysical studies (12)(13)(14)(15). The prototypic cyclotide kalata B1 (kB1) 7 is the most well studied cyclotide, and it has been shown to bind to (12) and disrupt phospholipid bilayers by a pore-forming mechanism (15).…”
mentioning
confidence: 63%
“…Studies with dodecylphosphocholine (DPC) micelles [47][48][49] showed that the hydrophobic regions of cyclotides are generally involved in membrane binding, but it has also been suggested that self-association of cyclotides (as well as membrane binding) is probably required to elicit a biological response. [37,39] Recent electrophysiological studies have confirmed that kalata B1 forms pores of ∼45 Å in diameter in membranes, consistent with a self-association mechanism. It has also been reported that different cyclotides have different membrane-binding modes.…”
Section: Kalata B1mentioning
confidence: 78%
“…Kalata B2 Kalata B8 vhl-2 A relationship between membrane binding and cytotoxic activity is also supported by several other chemical or biophysical studies, [14,[37][38][39] but all of the features involved in membrane binding have not yet been elucidated. Studies with dodecylphosphocholine (DPC) micelles [47][48][49] showed that the hydrophobic regions of cyclotides are generally involved in membrane binding, but it has also been suggested that self-association of cyclotides (as well as membrane binding) is probably required to elicit a biological response.…”
Section: Kalata B1mentioning
confidence: 92%
See 1 more Smart Citation
“…Bioactivities-The diverse biological activities of cyclotides have been proposed to arise from their ability to target, interact, and disrupt cell membranes (43)(44)(45)(46). In this work, we indirectly assessed the membrane-active properties of the novel panitides by using antimicrobial and cytotoxicity assays.…”
Section: Discussionmentioning
confidence: 99%